Feeding ground indications are based on species, seagrass density and existence of Dugong dugon in Hiri Island Sea, North Maluku, Indonesia. Issue 1 (October 2021) - Akbar, N; Marus, I; Ridwan, R; Baksir, A; Paembonan, R E; Ramili, Y; Tahir, I; Ismail, F; Wibowo, E S; Inayah,; Madduppa, H H; Subhan, B; et al.
Abstract: Seagrass ecosystems are located between mangrove ecosystems and coral reefs. Seagrass ecosystems are habitats and foraging area for many marine organisms. Eco-biological cycles in seagrass ecosystems are important for maintaining populations of many organisms. Seagrass at Hiri Island is distributed horizontally along the coast. This island is also a location where Dugong dugon is found North Maluku. Dugong dugon is a vurneable species that has been included in the IUCN and Appendix I Cites. This study aimed to identify species, density of seagrass and existence of Dugong dugong . The survey method used quadratic transect method to collect seagrass data. The Results found 6 species of seagrass at Hiri Island. Five species of those seagrass ( Cymodocea serrulata, Cymodecea rotundata, Halodule uninervis, Halodule pinifolia, Halophila spinulosa ) are known as food of Dugong dugon . The highest species density was shown by Halodule uninervis . The presence of Dugong dugon and its feeding trail was found during field survey. Information on seagrass species and Dugong dugon sightings location can be used for endangered species conservation policies. Management and conservation efforts need to be done to maintain seagrass ecosystem and Dugong dugon potential habitat at Hiri Island.